2018
DOI: 10.1101/466136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network remodeling induced by transcranial brain stimulation: A computational model of tDCS-triggered cell assembly formation

Abstract: Transcranial direct current stimulation (tDCS) is a variant of non-invasive neuromodulation, which promises treatment for brain diseases like major depressive disorder. In experiments, long-lasting aftereffects were observed, suggesting that persistent plastic changes are induced. The mechanism underlying the emergence of lasting aftereffects, however, remains elusive. Here we propose a model, which assumes that tDCS triggers a homeostatic response of the network involving growth and decay of synapses. The cor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 53 publications
4
27
0
Order By: Relevance
“…In experiments, transcranial direct current stimulation (tDCS) (Reato et al, 2013) and optogenetic stimulation (Cardin et al, 2010;Barthas et al, 2015) are often employed to perturb neural network activity and induce synaptic plasticity. We showed in another recent simulation study that the long-lasting after-effects of tDCS could be explained by homeostatic structural plasticity (Lu et al, 2019). In our present experimental study, we evaluated the time course of synaptic connectivity changes driven by optogenetic stimulation in mice.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In experiments, transcranial direct current stimulation (tDCS) (Reato et al, 2013) and optogenetic stimulation (Cardin et al, 2010;Barthas et al, 2015) are often employed to perturb neural network activity and induce synaptic plasticity. We showed in another recent simulation study that the long-lasting after-effects of tDCS could be explained by homeostatic structural plasticity (Lu et al, 2019). In our present experimental study, we evaluated the time course of synaptic connectivity changes driven by optogenetic stimulation in mice.…”
Section: Introductionmentioning
confidence: 89%
“…We used the same neuron model, synapse model, and network architecture, as published in our previous paper on transcranial electric stimulation (Lu et al, 2019). All the plastic neuronal network simulations of the current study were performed with the NEST simulator using a MPI-based parallel configuration (Linssen et al, 2018).…”
Section: Neuron Synapse and Network Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the interplay between Hebbian and homeostatic plasticity, we have recently demonstrated by simulations that homeostatic structural plasticity alone can lead to the formation of assemblies of strongly interconnected neurons, and that this process of memory formation has associative properties [12]. Moreover, we found that varying the strength of the stimulation and the fraction of stimulated neurons in combination with repetitive protocols can lead to even stronger assemblies [32]. In both papers, we used a structural plasticity model based on firing rate homeostasis, which had been used before to study synaptic rewiring linked with neurogenesis [6,7], and the role of structural plasticity after focal stroke [3,5] and after retinal lesion [2].…”
Section: Introductionmentioning
confidence: 91%
“…The baseline period is followed by an encoding period, in which C1 is paired with US, while C2 is always presented in isolation. Simultaneous stimulation of neurons in a recurrent network with homeostatic structural plasticity can lead to the formation of reinforced ensembles [12], which are strengthened by repetitive stimulation [32]. After the encoding period, each of the three neuronal ensembles has increased within-ensemble connectivity, as compared to baseline.…”
Section: Formation Of Memory Engrams By Homeostatic Structural Plastimentioning
confidence: 99%